A comparison of the functional connectome in mild traumatic brain injury and post‐traumatic stress disorder. Issue 2 (7th October 2022) - Klimova, Aleksandra; Breukelaar, Isabella A.; Bryant, Richard A.; Korgaonkar, Mayuresh S.
Abstract: Post‐traumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI) often co‐occur in the context of threat to one's life. These conditions also have an overlapping symptomatology and include symptoms of anxiety, poor concentration and memory problems. A major challenge has been articulating the underlying neurobiology of these overlapping conditions. The primary aim of this study was to compare intrinsic functional connectivity between mTBI (without PTSD) and PTSD (without mTBI). The study included functional MRI data from 176 participants: 42 participants with mTBI, 67 with PTSD and a comparison group of 66 age and sex‐matched healthy controls. We used network‐based statistical analyses for connectome‐wide comparisons of intrinsic functional connectivity between mTBI relative to PTSD and controls. Our results showed no connectivity differences between mTBI and PTSD groups. However, we did find that mTBI had significantly reduced connectivity relative to healthy controls within an extensive network of regions including default mode, executive control, visual and auditory networks. The mTBI group also displayed hyperconnectivity between dorsal and ventral attention networks and perceptual regions. The PTSD group also demonstrated abnormal connectivity within these networks relative to controls. Connectivity alterations were not associated with severity of PTSD or post‐concussive symptoms in either clinical group. Taken together, the similar profiles of intrinsic connectivity alterations in these two conditions provide neural evidence that can explain, in part, the overlapping symptomatology between mTBI and PTSD. Abstract : Post‐traumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI) over co‐occur and have overlapping symptoms even when a diagnosis of PTSD is not given following a mTBI. A challenge is articulating the degree to which overlapping or unique neurobiological changes are contributing to this. This study indicates wide‐spread, overlapping changes in the whole‐brain connectome co‐occur in PTSD and mTBI even when one occurs in the absence of the other.